AI 기반 에듀테크를 활용한 교육격차 해소방안 연구: 국어, 수학 교과를 중심으로 - 김혜란(Hye-Ran Kim); 김준호(Joon-Ho Kim); 김주현(Ju-Hyeon Kim); 노상민(Sang-Min Noh); 박정호(Jung-Ho Park) (디지털콘텐츠학회논문지, 2024)
본 연구는 농어촌 지역의 초등학생을 대상으로 자율 학습 지원과 피드백이 가능한 AI 기반 에듀테크가 국어, 수학 교육에서 교육격차 해소에 어떠한 영향을 미치는지 조사하였다. 이를 위해 국어과에서는 대화형 생성 AI를 첨삭 도구로 활용한 글쓰기 프로그램을 적용하였고, 수학과에서는 ITS(지능형 교수 시스템)를 보조도구로 활용하였다. 이를 통해 각각 글쓰기 능력과 학업 성취도가 향상되었음을 확인할 수 있었다. 또한, 연구 대상에게 AI 기반 에듀테크 적용 전후로 설문조사를 실시하였고, 그 결과 이러한 교육적 접근이 학생의 정의적 영역과 환경적 영역에 긍정적인 영향을 미친다는 것을 발견하였다. 본 연구는 교육격차 요인에 대한 원인 분석에 그쳤던 기존 선행연구와 달리 AI 기반 에듀테크를 적용한 후 학생의 실제 성취 데이터와 정의적 영역, 환경적 영역에서 교육격차를 해소하는 방안을 제시하였다. This study investigated how AI-based Edtech, which provides autonomous learning support and feedback to elementary school students in rural areas, affects the closing of educational gaps in Korean language and Math education. To this end, a writing program that uses interactive generation AI as a correction tool was applied in the Korean language department, and an ITS(Intelligent Teaching System) was used as an aid in the mathematics department. Furthermore, the study subjects were surveyed before and after the application of AI-based Edtech, and the results showed that this educational approach positively impacted the definitional and environmental domains of the students. Unlike previous studies that only analyzed the causes of the educational gap, this study provides a solution to the educational gap in the definitional and environmental domains based on the actual achievement data of students after applying AI-based Edtech. KCI Citation Count: 7